The Use Of Talking Stick Learning Method In Improving Learning Outcomes Of The Course Of Aqidah And Morals In Grade 5 At Sampang State Islamic Elementary School - Maulana, Mohammad Fiki; Maghfiroh, Muliatul (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
This study aims to improve students' learning achievements in the subject of Aqidah Akhlak at MIN Sampang by implementing the Talking Stick method. Based on initial observations and interviews, it was found that many students had not yet reached the Minimum Mastery Criteria (KKM) of 75, which was due to a lack of focus and monotonous teaching methods. This research uses a Classroom Action Research (CAR) approach with 18 fifth-grade students as the subjects. The study was conducted in two cycles, with each cycle consisting of two meetings in the first cycle and one meeting in the second cycle, following the Kemmis and McTaggart model procedure, which includes four stages: planning, action, reflection, and observation. The results of the study showed a significant improvement in students' learning outcomes after the application of the Talking Stick method. In the final cycle, 15 students achieved the KKM with an average class score that increased to 80. In conclusion, the Talking Stick method was proven effective in improving students' learning outcomes in the subject of Aqidah Akhlak. The improvement in learning outcomes was reflected not only in higher average scores but also in the increased participation and engagement of students in the learning activities. Therefore, this study contributes to the improvement of the quality of learning at MIN Sampang and recommends the use of the Talking Stick method as an alternative to improve students' learning outcomes in the subject of Aqidah Akhlak. Keywords: Talking Stick method, learning outcomes, faith, and morals.